The Buckley potteries : recent research and excavation - Jones, Nigel, 1961- (Archaeopress Archaeology, 2019)
The small town of Buckley, in Flintshire, has been the focus for a regional pottery industry for at least 600 years, from the medieval period to the mid-20th century. However, despite Buckley's impressive industrial past, a visit to the town today reveals little evidence to suggest the extent and importance of what was once a major industry supplying traditional earthenware. This book is based on the results of recent research and excavation which has enhanced our understanding of the Buckley potteries, identifying over 30 individual production sites from documentary and cartographic sources. It considers the factors that influenced the siting and development of the industry, how it changed through time and the reasons for its eventual demise.